Development of a Rheumatoid Arthritis Education Program using the PRECEDE_PROCEED Model - Kaveh Bahmanpour; Mohammad Ali Morowatisharifabad; Haidar Nadrian (Tabriz University of Medical Sciences, 2011)
Background: In order to help rheumatoid arthritis (RA) patients in carrying out and attaining relevant self-care behaviors and adaptation to the physical limitations of this disease and, conse-quently, promoting their level of health status, an education program based on the PRECEDE component of the PRECEDE-PROCEED model targeting patients with RA was developed. This paper describes the planning of a RA Patient Education Program (RAPEP) designed to promote their quality of life.Methods: The development of the program began with a comprehensive review of the literature. This included a review of the signs and symptoms of RA, accompanying functional disabilities, previous educational programs and the effect of the disease on the patient's quality of life. Be-sides, in order to help inform RAPEP program development, and organize the survey according to the factors identified in the PRECEDE model a cross-sectional survey was applied on a non-prob-ability sample of 181 outpatients in Yazd, center of Iran.Results: The quality of life (QOL) problem identified was the considerable low role functioning, health perception and physical functioning due to chronic pain. One of the most significant modi-fiable behavioral factors impacting pain and functional limitations was self-care behaviors in RA patients. Higher level of knowledge, attitude, self-efficacy, enabling factors and social support is associated with better self-care behavior.Conclusions: The PRECEDE component of the PRECEDE-PROCEED model provided a com-prehensive conceptual framework for the development of RAPEP aiming at RA patients in Yazd. Further research to evaluate this educational program is suggested.